EFFECT OF ADDITION OF FEED Tenebrio molitor TO THE GROWTH OF QUAIL (Coturnix-coturnix japonica) - I. V., MAHA; ., ELFRIDA; SARJANI, T. M. (Majalah Ilmiah Peternakan, 2022)
The study aimed to determine the effect of adding Tenebrio molitor to the growth of quail (Coturnix-coturnix ja- ponica). The research approach is quantitative. This type of experimental research with a a completely randomized design (CRD) consisted of 4 treatments and 5 repetitions. The treatments used were P0 (control), P1 (larvae eating vegetable waste), P2 (larvae eating fish waste), P3 (larvae eating vegetable + fish waste). The parameters in this stu- dy were quail consumption, quail growth, and quail egg weight. The data were analyzed using the Two-way ANOVA test and Duncan’s Advanced Real Distance test at a significant level of 0.05. The results showed that the growth of quail did not interact between the feeding factor of Tenebrio molitor larvae that ate organic waste and the quail age factor, namely Fcount (1.47) < Ftable (1.88). From the results of the study, it can be concluded that the most optimal feed is P3 (larvae eat vegetable + fish waste) seen from the growth of quail, quail consumption, and quail egg weight.